Perceptions of English Language Students on the Relevance of ‘EFL’, ‘ESL’ and Other Such Terms in Contemporary Turkish Contexts - Ironsi, Chinaza (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
Over the years, there has been an ongoing debate on the relevance of certain terms like ESL, EFL. Several linguists have argued that these terms do not represent a wide range of language users under varying circumstances, given their various proficient language competence levels. In a bid to unveil the extent to which this presupposition applies to the use of ESL and EFL terms. A group of 36 participants from a school in North Cyprus was purposively chosen for this quantitative study. Four research questions were to be investigated. Questionnaires were used to collect vital data from the participants on their perceptions on terms like ESL and EFL. After analysis, results were collected, analysed and used to make cases for redefining the concepts of ESL and EFL terms, especially within the Turkish-Cypriot setting. A notable finding of this study was that the participants believed that terms like EFL ESL do not adequately define their language status. They further suggested that more appropriate terms should be used. The study suggested using English as an international and intranational language instead of the former terms, among other suggestions. This study adds to the corpus of research showing that while acronyms like EFL and ESL are relevant in English language education, more emphasis should focus on improving learner's four language skills which directly impacts their performance and production of the target language.